Indonesia Pemberdayaan Masyarakat Melalui Pengembangan E-Commerce Bandeng Presto Berbasis Digital dan Pelatihan Kewirausahaan Desa Lomuli Lemito - Drajana, Ivo Colanus Rally; Nasrul , Muhammad; Fitriyanti Bulotio, Nur (Politeknik Negeri Jember, 2026)
The development of digital technology opens up opportunities for people to utilize digital-based e-commerce as a means of promotion and sales. One business that can be developed through community empowerment is presto milkfish. Milkfish processing was chosen as one of the culinary products developed by the Casamur UKM of Lomuli Village because the fish harvest in Lomuli Village is quite abundant. The PMP Team of Pohuwato University collaborated with the Casamur UKM of Lomuli Village in improving the development of the milkfish processing business by looking at the problems faced by partners, namely technology adoption, human resources and marketing aspects. The aim of implementing this PMP is to increase the knowledge, skills and income of the Casamur UKM in Lomuli Village in the presto milkfish business. The method used in this PMP activity is in technology adoption by carrying out mentoring and counseling related to digital-based E-Commerce for Casamur SME partners in Lomuli Village, in the human resource aspect by carrying out training activities on making presto milkfish so that partner skills can improve and in the marketing aspect, namely by carrying out digital marketing-based entrepreneurship training activities by creating a Google Business platform and the percentage of presto milkfish business income. The sustainability of this program is to provide assistance and guidance to improve the capabilities and skills of the Casamur SME in Lomuli Village in processing and marketing processed milkfish products. The results of the PMP activity are that the Casamur Lomuli Village UKM partners know and understand the adoption of innovative use of technology in the production of presto milkfish and have skills in conducting digital-based e-commerce marketing as well as a 50% increase in revenue and establishing partner collaborations.